2(3x-1)+3(3y-y-x)=

Simple and best practice solution for 2(3x-1)+3(3y-y-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-1)+3(3y-y-x)= equation:


Simplifying
2(3x + -1) + 3(3y + -1y + -1x) = 0

Reorder the terms:
2(-1 + 3x) + 3(3y + -1y + -1x) = 0
(-1 * 2 + 3x * 2) + 3(3y + -1y + -1x) = 0
(-2 + 6x) + 3(3y + -1y + -1x) = 0

Reorder the terms:
-2 + 6x + 3(-1x + 3y + -1y) = 0

Combine like terms: 3y + -1y = 2y
-2 + 6x + 3(-1x + 2y) = 0
-2 + 6x + (-1x * 3 + 2y * 3) = 0
-2 + 6x + (-3x + 6y) = 0

Combine like terms: 6x + -3x = 3x
-2 + 3x + 6y = 0

Solving
-2 + 3x + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 3x + 2 + 6y = 0 + 2

Reorder the terms:
-2 + 2 + 3x + 6y = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 3x + 6y = 0 + 2
3x + 6y = 0 + 2

Combine like terms: 0 + 2 = 2
3x + 6y = 2

Add '-6y' to each side of the equation.
3x + 6y + -6y = 2 + -6y

Combine like terms: 6y + -6y = 0
3x + 0 = 2 + -6y
3x = 2 + -6y

Divide each side by '3'.
x = 0.6666666667 + -2y

Simplifying
x = 0.6666666667 + -2y

See similar equations:

| 3(c-11)=12 | | -2y+0=6y | | (4x-10)(-2)= | | 140=3x+8x+8 | | 5a+7=3a+39 | | 6w-10+-18w= | | 2(30)+8= | | 4+8=36 | | 1-(1/2)(-x+5)=2+3(1-x) | | 15-4x=32 | | 7x-5(2x+2)=-19 | | -14p=156 | | 5+5y-5y=5 | | 17+x=3+17 | | -2(x-8)=6(x+4)-8 | | 5x+8-7x-12= | | y=2x^2+36x+168 | | 5y+6x-3y-5x+4x= | | 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 |

Equations solver categories